Femtosecond laser inscription of Bragg and complex gratings in coated and encapsulated silica and low-loss polymer optical fibers - Kalli, Kyriacos; Lacraz, Amédéé; Polis, Michael; Othonos, Andreas (My University, 2015)
The development of wavelength filters, such as Bragg and superstructure gratings in glass and polymer optical fibers, using a femtosecond laser is reported. By using a femtosecond laser operating in the green, which offers greater inscription efficiency, we demonstrate the reliable inscription of Bragg and superstructure gratings in coated silica and low-loss CYTOP polymer optical fibers. We employ line by line and point by point inscription methods, allowing for multiple and overlapping gratings in the fiber core. Moreover, we demonstrate a novel fibre Bragg grating inscription technique to modify and add versatility to an existing, encapsulated optical fiber pressure sensor.
Keywords: Bragg gratings; Femtosecond laser inscription; Optical fiber sensors; Polymer optical fiber